PENGARUH PENERAPAN METODE PEMBELAJARAN COLLABORATIVE PROBLEM BASED LEARNING (CPBL) TERHADAP KREATIVITAS ANAK DALAM BERMAIN KOMPUTER - -, PARWOTO (Jurnal Pendidikan Usia Dini, 2017)
The problem continues to be the development of children's creativity experts talk of education of preschool children, especially regarding the optimization function of the right hemisphere as a function of the creativity and imagination of children. On the basis of this assumption, the development of creativity is very important in earnest in early childhood education, especially in early childhoodThis study aims to determine the effect of applying the method of collaborative problem-based learning to play computer creativity of children in kindergarten Dharmawanita Lotus Makassar. This research is a kind of experimental control group design and samples were taken through a multi -stage random sampling. The results showed that the children's creativity in playing computer games for children who attend the learning method CPBL included in the high category, while the children's creativity in playing computer games for a group of children who attend individual tutorial learning methods included in the medium category. No effect of the application of collaborative learning method of problem-based learning to the creativity of children in kindergarten children play on the computer. Keywords: CPBL methods, creativity, computer, kindergarteen